Beyond Performance Management - Hope, Jeremy; Player, Steve (Ascent Audio, 2020)
There's a bewildering array of management tools out there. And they all promise to help you excel at the toughest parts of your job: defining your organization's strategic direction, managing customers and costs, and boosting workforce performance. But just 30 percent of these tools deliver as intended. Why? As Jeremy Hope and Steve Player reveal in Beyond Performance Management, while many tools are sound in theory, they're misused by most organizations. For example, executives buy and implement a tool without first asking, "What problem are we trying to solve?" And they use tools to command and control frontline teams, not empower them-a serious and costly mistake. In this eminently useful, clear-eyed book, the authors critically review dozens of well-known management tools-from mission statements, balanced scorecards, and rolling forecasts to key performance indicators, Six Sigma, and performance appraisals. They explain how to select the right tools for your organization, how to implement them correctly, and how to extract maximum value from each. Brimming with rigorous analysis and solid advice, Beyond Performance Management helps you swiftly gauge the value of each management tool, as well as navigate the increasingly crowded field of offerings-so the tools you select deliver fully on their promise.